The execution of Muslim wills (Wasiyyah) in Malaysia: A way to evade islamic inheritance (Fara’iḍ) (Pelaksanaan wasiat di Malaysia: Satu cara pembahagian harta pusaka (Faraid)) - Halim, Akmal Hidayah; Mohd Noor, Nor Azlina; Mohd Salim, Wan Noraini (International Islamic University Malaysia (IIUM), 2020)
In cases where a Muslim dies and leaves a will (waÎiyyah), the jurisdiction to deal with the deceased’s estate lies with the Civil High Court and Shariah Court as far as the procedural and substantive laws are concerned respectively. The existence of the dual jurisdiction has given rise to the conflict of jurisdiction between the High Court and the Shariah Court particularly when an application for the grant of probate from the High Court is required in order to formalise the appointment of the wasi which must be made via a valid will (wasiyyah). In this context, the law is silent as to the requirement for such a will to be firstly validated by the Shariah Court before probate could be granted to the wasi. This paper seeks to analyse the jurisdiction of the High Court and Shariah Court to examine the law and procedure relating to the execution of Muslim willsin Malaysia. The study adopts a content analysis by examining the existing prima-ry and secondary materials including the statutory provisions provided in the Probate and Administration Act 1959, Wills Act 1959, Rules of Court 2012, Muslim Will Enactments and case law. The findings show that the absence of a legal provision relating to the requirement for the reference of a Muslim’s will to the Shariah Court before the issuance of the grant of probate would open up room for the execution of a wasiyyah which does not comply with the Islamic law on wills, thus avoiding the distribution of the estate to be made according to Islamic inheritance